Fibroblast growth factor receptor 3 mutation promotes HSPB6-mediated cuproptosis in hypochondroplasia by impairing chondrocyte autophagy - Jing Chen; Dan He; Chengrun Yuan; Na Li; Baohong Shi; Conway Niu; Jiangfei Yang; Liangkai Zheng; Lin Che; Ren Xu (Journal of Orthopaedic Translation)
Background: Hypochondroplasia (HCH) is a prevalent form of dwarfism linked to mutations in the fibroblast growth factor receptor 3 (FGFR3) gene, causing missense alterations. We previous report was the first to identify FGFR3(G382D) gain-of-function variants with a positive family history as a novel cause of HCH. However, the precise contribution of FGFR3 to the pathogenesis of HCH remains elusive. Methods: We generated an Fgfr3 (V376D) mutation mouse model using CRISPR/Cas9 technology and performed proteomic analyses to investigate the molecular mechanisms and potential therapeutic targets of HCH. Radiography and micro-computed tomography were employed to assess the bone-specific phenotype in Fgfr3 (V376D)mutant mice. Immunofluorescence, western blotting, and flow cytometry were used to systematically investigate the underlying mechanisms and therapeutic targets. Results: We observed that Fgfr3 (V376D) mutant mice exhibit a bone-specific phenotype, with symmetrically short limb bones, partially resembling the dwarfism phenotype of patients with HCH. We demonstrated that the mutant-activated FGFR3 promotes heat shock protein B 6 (HSPB6)-mediated cuproptosis by inhibiting chondrocyte autophagy both in vivo and in vitro. Additionally, we revealed that FGFR3 (G382D) mutation leads to enhanced ERK signaling, increased Drp1-mediated mitochondrial fission, and upregulated cuproptosis-related protein ferredoxin 1 (FDX1). Furthermore, genetic and pharmacological inhibition of the HSPB6-ERK-Drp1-FDX1 pathway partially alleviate the phenotypes of FGFR3 mutants. Conclusions: Our study provides the first evidence for the pathogenicity of a gain-of-function mutation in FGFR3 (G382D) using mouse and cell models, and it underscores the potential of targeting the HSPB6-ERK-Drp1-FDX1 axis as a novel therapeutic approach for HCH. Translational potential of this article: We first demonstrate that impaired autophagy and enhanced cuproptosis are pivotal in the pathogenesis of HCH. This study not only enlarged the therapeutic potential of targeting cuproptosis for treating FGFR3 mutation-related HCH but also provided a novel perspective on the role of the HSPB6-ERK-Drp1-FDX1 signaling pathway in the development of HCH. Consequently, this article provides valuable insights into the mechanisms and treatment strategies for FGFR3 mutation-related chondrodysplasia.